Clinical Effectiveness and Cost of a Hospital-Based Fall Prevention Intervention: The Importance of Time Nurses Spend on the Front Line of Implementation. (November 2017) - Nuckols, Teryl K.; Needleman, Jack; Grogan, Tristan R.; Liang, Li-Jung; Worobel-Luk, Pamela; Anderson, Laura; Czypinski, Linda; Coles, Courtney; Walsh, Catherine M.
Abstract : OBJECTIVE: The aim of this study is to evaluate the clinical effectiveness and incremental net cost of a fall prevention intervention that involved hourly rounding by RNs at 2 hospitals. BACKGROUND: Minimizing in-hospital falls is a priority, but little is known about the value of fall prevention interventions. METHODS: We used an uncontrolled before-after design to evaluate changes in fall rates and time use by RNs. Using decision-analytical models, we estimated incremental net costs per hospital per year. RESULTS: Falls declined at 1 hospital (incidence rate ratio [IRR], 0.47; 95% confidence interval [CI], 0.26-0.87; P = .016), but not the other (IRR, 0.83; 95% CI, 0.59-1.17; P = .28). Cost analyses projected a 67.9% to 72.2% probability of net savings at both hospitals due to unexpected declines in the time that RNs spent in fall-related activities. CONCLUSIONS: Incorporating fall prevention into hourly rounds might improve value. Time that RNs invest in implementing quality improvement interventions can equate to sizable opportunity costs or savings.